Unjuk Kerja Motor Starter Pada Pengoperasian Mesin Induk KM. Bandar Nelayan 519 - Fahriadi Pakaya; Yurika Nantan; Marinus S Tappy; Junardi Junardi; Wisna Saputri Alfira (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The starter motor is one component of the starting system on the main engine which is used as an initial drive so that the main engine can rotate and carry out the combustion process in the combustion chamber. The aim of the research was to determine the performance of the starter motor during the operation of the main engine KM. Bandar Nelayan 519 through a quantitative approach. The results of measurements and calculations show the rotational speed obtained is 462.4 rpm, the power is 7.5Kw comes from two batteries with a voltage of 24V and a capacity of 200 Ah. The torque produced by the starter motor to drive a 10-cylinder Nissan diesel engine that has 132 gears is 443.24 Nm with an electric current of 312 A and 0.07 Ω resistance. This research calculates the performance of the starter motor because it is very influential on the starting process of the main engine, where weak performance will make it difficult to start the engine.